Risk-management challenges for civil society in Santa María de Huachipa and Cajamarquilla following the overflowing of the Huaycoloro River - Illanes Calderón, Christian (2018)
We seek to determine the degree of incidence of civil society groups in the design and implementation of the Disaster Risk Management policy in Santa María de Huachipa and Cajamarquilla. Both areas are located in the Lurigancho-Chosica district, specifically in the Huaycoloro river gorge. They were affected by the overflow of that river between February and March 2017. As a result, infrastructure losses were reported. The methodological proposal of this study follows a qualitative approach. It is a case study. Information will be gathered in depth through semi-structured interviews with members of homeowner associations and officials of the municipalities of Huachipa and Chosica before and during the disaster (for the implementation of the current policy) and after the disaster (for the design and implementation of an improved risk-reduction alternative). The hypothesis is that homeowner associations have a low incidence in the Disaster Risk Management policy. Given the «market governance» scenario that prevails in the studied areas, these associations are limited to a secondary role. The municipal authority only asks them for information, but does not encourage them to play a more proactive role in making decisions.